Humoral antimalaria immune response in Nigerian children exposed to helminth and malaria parasites - Adukpo, Selorme; Adedoja, Ayodele; Esen, Meral; Theisen, Michael; Ntoumi, Francine; Ojurongbe, Olusola (Frontiers in Immunology, 2022)
Background: Malaria and helminthic parasites are endemic in tropical countries, and co-infections might influence host-parasite interactions. In this community-based cross-sectional study, the effect that the presence of soil-transmitted helminths (STH) (Hookworm, Hymenolepis nana) and Schistosoma haematobium infections could have on the immunoglobulin (Ig) candidate protein of the malaria vaccine GMZ2 levels was evaluated. Methods Blood, stool, and urine samples were collected from 5-15-year-old children to diagnose P. falciparum (Pf), STH, and Schistosoma haematobium, respectively. Identification and quantification of the parasite load of STH and S. haematobium were achieved by light microscopy. A polymerase chain reaction was carried out to detect submicroscopic infections of P. falciparum. Plasma levels of GMZ2 specific IgG and its subclasses were quantified by ELISA. Results: The median level of total IgG in individuals with co-infection with Pf / H. nana was significantly lower in the mono-infected group with Pf (p = 0.0121) or study participants without infection (p=0.0217). Similarly, the median level of IgG1 was statistically lower in Pf/H. nana group compared to Pf-group (p=0.0137). Equally, the Pf/Hookworm infected individuals posted a lower level of IgG2 compared to the Pf group (p=0.0348) and the no infection group (p=0.0144). Spearman rank correlation analyses indicated positive relationships between the densities of H. nana (ρ=0.25, p=0.015) and S. haematobium (ρ=0.36, p<0.0001). Conclusions: Hookworm and H. nana infections are associated with reduced GMZ2 specific IgG levels. This study shows the possible manipulation of immune responses by helminths for their survival and transmission, which may have serious implications for vaccine development and deployment in helminth-endemic regions.